PERAN PESANTREN DALAM MENGHADAPI PERKEMBANGAN TEKNOLOGI (STUDI KASUS DI PONDOK PESANTREN NURUL HIDAYAH, KOTA SEMARANG) - Aida, Azkiya Nur (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Islamic boarding schools have existed and developed since the beginning of the spread of Islam in Indonesia. This boarding school is the oldest Islamic educational institution in Indonesia and is considered an Indonesian cultural product that can form a moral and civilized generation. In this modern era, Islamic boarding schools are one of the Islamic educational institutions that cannot be separated from the influence of technology because technology has now become the main driving force in human progress and civilization in almost all human activities. This study aims to determine the technological culture formed by the use of gadgets and the impact of gadget use for students in the Nurul Hidayah Islamic Boarding School in Semarang. The method used in this research used a qualitative method by applying descriptive data output or interviews. The results show that Nurul Hidayah Islamic Boarding School can be open to the use of technology in the boarding school environment by implementing various rules for the use of technology.